Ana Marta González, Claves de ley natural, Madrid: Rialp, 2006, 168 páginas - Massini Correas, Carlos I. (2006)
Fil: Massini Correas, Carlos I. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina